1993
DOI: 10.1109/75.196031
|View full text |Cite
|
Sign up to set email alerts
|

A coplanar-to-microstrip transition for W-band circuit fabrication with 100- mu m-thick GaAs wafers

Abstract: Results on a via-hole interconnect that links a coplanar waveguide (CPW) on one side of a 100-mm thick GaAs substrate to a microstrip line on the opposite side are presented. The measured insertion loss of a pair of back-to-back connections is 0.3 dB between 26.5 and 40 GHz. A lumped-element equivalent circuit of this via-hole interconnect has been extrapolated to W-band and used to design amplifiers at 94 GHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…9. The microstrip and CPW are interfaced through a single via connecting the signal traces with the transmission lines (TLs) sharing the same ground plane [55], see Fig. 9.…”
Section: Common Ground Microstrip-to-coplanar Waveguide Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…9. The microstrip and CPW are interfaced through a single via connecting the signal traces with the transmission lines (TLs) sharing the same ground plane [55], see Fig. 9.…”
Section: Common Ground Microstrip-to-coplanar Waveguide Transitionmentioning
confidence: 99%
“…9. Unlike in [55], the design geometry in our example is defined with the CPW ending on the rectangular slot and the straight barrel via with no pads. The lengths of the input TLs are 15.0 mm each.…”
Section: Common Ground Microstrip-to-coplanar Waveguide Transitionmentioning
confidence: 99%
“…One is by physical contact and the other is by electromagnetic coupling. Via-holes, bonding wires, or abrupt discontinuities in the conductor are usually required in physical contact transitions [4], [5]. In multilayer circuit design, via-holes are often introduced between the outer metal layer and the inner metal layer for circuit measurement and interconnection with other circuits.…”
Section: Introductionmentioning
confidence: 99%
“…The distance between the probe contact region and the via hole is 150 µm, the via hole diameter is 15 µm, and the distance from the merged ground plane to the via hole is 50 µm. It is noted that this transition between CPW and microstrip and/or inverted microstrip has been successfully used over a wide frequency range [11], [12]. It has been reported that resonances within the CPW to microstrip transition can be established if the dimensions are large relative to the wavelength [13].…”
Section: Introductionmentioning
confidence: 99%